Faktor-Faktor Mempengaruhi Minat Wisatawan Dalam Pemilihan Hotel Bunda Syariah Pada Masa New Normal - Afrilian, Pepy; Hanum, Latifah (Politeknik Negeri Padang, 2022)
The Covid-19 virus has changed the order of human life and this situation must be adapted to the tourism industry, one of which is the Sharia hotel industry in Bukittinggi, to be able to survive the Covid-19 pandemic, what needs to be done by analyzing the interest of tourists to still choose Sharia hotels even in the new normal during the Covid-19 pandemic. The purpose of this study is to find out and analyze what factors affect tourists' interest in the selection of Syariah hotels in the new normal period in 2021 with quantitative methods and data analysis techniques used is to use the stages of affirmative factor analysis, namely by formulate problems, arrange correlation matrix, determine the number of factors then rotate those factors. This study used 6 factors, namely facility factors, service factors, religiosity factors, price factors, location factors, and standard covid-19 factors. The results showed that having a positive regression and t-value coefficient means a significant effect on the interest of tourists staying in Bunda Sharia hotels, namely facility factors, service factors, religiosity factors, location factors, and price factors. The study also revealed that the covid-19 standard factor has a regression coefficient of -0.33 and a t-value of -2.12 means that the standard factor of covid-19 becomes a factor that affects tourist interest but significantly affects its influence.